2011
DOI: 10.1111/j.1740-8709.2011.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

The role and influence of grandmothers on child nutrition: culturally designated advisors and caregivers

Abstract: Improving the nutritional status of infants and young children in developing countries depends to a significant extent on adoption of optimal nutrition-related practices within the context of the household. Most policies, research and programmes on child nutrition in non-Western societies focus narrowly on the mother-child dyad and fail to consider the wider household and community environments in which other actors, hierarchical patterns of authority and informal communication networks operate and influence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
240
2
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(274 citation statements)
references
References 45 publications
21
240
2
11
Order By: Relevance
“…Involving the wider community, including men and grandmothers in community-based education programmes in Malawi and elsewhere would ensure that all those involved in the treatment-seeking process are included [29, 31, 33, 34]. The role of older women should also be harnessed in behaviour change strategies [35]; involving grandmothers in health education programmes has been seen to lead to improvements in the education messages they give to mothers, and mothers’ health seeking behaviour [36]. Such interventions should be used to challenge, rather than reinforce, the underlying gender and generational inequalities that shape the treatment-seeking process, through working to promote the position of junior women and improve their power and autonomy in the treatment-seeking processes, particularly in remote villages [1, 7, 25, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Involving the wider community, including men and grandmothers in community-based education programmes in Malawi and elsewhere would ensure that all those involved in the treatment-seeking process are included [29, 31, 33, 34]. The role of older women should also be harnessed in behaviour change strategies [35]; involving grandmothers in health education programmes has been seen to lead to improvements in the education messages they give to mothers, and mothers’ health seeking behaviour [36]. Such interventions should be used to challenge, rather than reinforce, the underlying gender and generational inequalities that shape the treatment-seeking process, through working to promote the position of junior women and improve their power and autonomy in the treatment-seeking processes, particularly in remote villages [1, 7, 25, 29].…”
Section: Discussionmentioning
confidence: 99%
“…É possível que o impacto da intervenção tivesse sido maior se ela fosse mantida ao longo do primeiro ano de vida da criança, com mais sessões abordando a alimentação complementar. A decisão de incluir as avós maternas na intervenção, quando em coabitação, foi baseada no fato de que, segundo alguns estudos, as avós maternas desempenham importante papel na escolha alimentar de seus netos, tanto na decisão quanto ao momento adequado para iniciar a alimentação como participando diretamente da seleção e do preparo dos alimentos 15,18,20,33,34,35,36 . Contudo, na amostra deste estudo, a coabitação com as avós maternas, tanto no grupo controle quanto no grupo intervenção, não interferiu no cumprimento dos Dez Passos nos filhos das mães adolescentes.…”
Section: Discussionunclassified
“…Pesquisas conduzidas em diferentes populações 14,15,16,17,18,19,20 , inclusive na do presente estudo 18,19 , sugerem que maternidade na adolescência e coabitação com a avó materna da criança são possíveis fatores de risco tanto para menor duração do AM, quanto para práticas alimentares inadequadas no 1 o ano de vida. Tal fato se deve, provavelmente, à dependência econômica das adolescentes em relação à sua família, o que muitas vezes implica, além da coabitação, a participação direta das avós na decisão, seleção e preparo dos alimentos 20 ; por isso, este estudo teve como objetivo testar o efeito de uma intervenção pró-AM e pró-alimentação complementar saudável, direcionada a mães adolescentes e avós maternas das crianças quando em coabitação, sobre a qualidade da alimentação das crianças no primeiro ano de vida, avaliada pelo cumprimento dos Dez Passos para uma Alimentação Saudável: Guia Alimentar para Crianças Menores de Dois Anos.…”
Section: Introductionunclassified
“…Surveys conducted in several cultural contexts indicate that grandmothers have influence and involvement on the child’s diet 1 . A qualitative study with teenage mothers and grandmothers held in Baltimore, USA, showed that most grandmothers studied played dominant role in deciding what the child should eat as well as in the moment of the introduction of solid food 3 .…”
Section: Discussionmentioning
confidence: 99%